Cashless India: Cutting Wings to Development Perspective (Trinity Journal of Management, IT & Media (TJMITM), 2017)
Demonetization is when a currency note of a particular  denomination ceases to be a legal tender. It can also be referred  to as scrapping or phasing out of certain currency notes. In India,  every household has included demonetization in their daily  routine since 8th November 2016, time when the government  pulled the old Rs500 and Rs1000 notes out of circulation. One of the major questions that arise in the mind of every  individual is that what led to Demonetization? There are 3 major  reasons for the same:- To curb black money in the economy. To encourage cashless transactions. To reduce corruption practices like Hawala.  Every cause has pros and cons, so when we talk about  Demonetization it itself has some pros and cons. But, the  immediate execution of this move has created more negative  outcomes than positive as they are largely directed onto the  common man. Those who do not have easy access to banks and  post offices are finding it difficult to accept this change. Till date,  new currency notes continue to be in short supply, causing  difficulties for people to carry out day-to-day transactions. The motive behind this sudden execution of Demonetization in  India was to get hold of Black money hoarders but it has led to  many shortcomings, if this step would have been made at the  later stages, the results would have been more positive. In this  research paper, we want to discuss the impact of recent  demonetization on the Indian system
Keywords: Demonetization; Corruption; Cashless Transactions; Black Money; Development